Isoflavone-enriched soybean leaves (Glycine max) restore loss of dermal collagen fibers induced by ovariectomy in the Sprague Dawley rats - Dae Young Yoo; Cheng-liang Xie; Joo Yeon Jeong; Ki Hun Park; Sang Soo Kang; Dong Hoon Lee (Laboratory Animal Research, 2024)
Abstract Phytoestrogens, such as isoflavones, are known for their capacity to simulate various physiological impacts of estrogen in the human body. Our research evaluated the effects of isoflavone-enriched soybean leaves (IESL) on collagen fiber loss prompted by ovariectomy in Sprague Dawley (SD) rats, thereby simulating menopausal changes in women. IESL, bolstered with an increased concentration of isoflavones through a metabolite farming process, contained a significantly higher amount of isoflavones than regular soybean leaves. Our results indicate that the administration of IESL can counteract the decrease in relative optical density and dermal thickness of collagen fibers caused by ovariectomy in SD rats, with more pronounced effects observed at higher isoflavone dosages. These outcomes suggest that soybean leaves rich in isoflavones may hold potential benefits in combating collagen degradation and skin aging symptoms related to menopause. Further research is needed to fully understand the exact molecular pathways at play and the potential clinical relevance of these findings.